Pengembangan Sistem Informasi CRM Berbasis Web untuk Manajemen Pelanggan dan Riwayat Transaksi pada UMKM Toko Sumber Rejeki Kecamatan Gubug Kabupaten Grobogan - Mayasari, Putri; Rusito, Rusito; Wahyuning, Sri (LPPM Universitas Sains dan Teknologi Komputer, 2026)
The development of information and communication technology encourages Micro, Small, and Medium Enterprises (MSMEs) to manage data more effectively, efficiently, and integratively to create consumer loyalty. Efforts can be made using a web-based Customer Relationship Management (CRM) Information system to manage customer data and transaction history in an integrated, effective, and efficient manner. The many complaints from several stores in Grobogan Regency, especially Toko Sumber Rezeki, regarding errors in inputting consumer data, data loss, and difficulties in preparing sales reports, prompted the author to conduct this research with the aim of providing practical contributions to MSMEs in managing data effectively by using a CRM (Customer Relationship Management) information system. The method used in this research is Research and Development (R&D) with a Waterfall software development model that includes the stages of needs analysis, system design, implementation, testing, and maintenance. The system was developed using PHP with the Laravel 11 framework and a MySQL database. The system's main features include customer data management, real-time transaction recording, integrated purchase history, a sales summary dashboard, and reports that can be exported to PDF and Excel. The results of this study indicate that the system meets user needs and helps improve recording efficiency and data accuracy. Therefore, the designed system can support data-driven decision-making and improve the quality of customer service at the Sumber Rejeki Store in Grobogan Regency.